The Effectiveness of Mood Board Learning Media in Developing Ideas in Fashion Design Courses - Aryati, Yulia; Efi, Agusti; Yudistira, Sukma (JURNAL PENDIDIKAN DAN KELUARGA, 2024)
Learning media, in general, is a process tool that stimulates the thoughts, feelings, attention, and abilities or skills of students so that they can encourage the learning process. In the Fashion Design course, students are required to be able to create a design based on various sources of creative and innovative ideas. To create an innovative design, we need a learning media that is able to determine goals, directions, and guidelines in creating works, one of which is the mood board media. This study aimed to determine the effectiveness of a mood board learning media for home economics undergraduate students. Concentration of Fashion in developing design ideas. This study uses the mixed method (combined method: qualitative and quantitative). According to the results of the calculation of the 19 items related to the effectiveness of using the mood board learning media that the author gave to 34 students in the class, they were included in the "effective" category. In this study, it can be interpreted that the effectiveness of the use of mood board learning media in the Fashion Design course for S1 PKK students concentrating on Fashion Design has been effectively implemented.